Le Canada - Champlain, Samuel de, 1574-1635 (Paris, France, 1677)
Colour. Shows Eastern North America between latitude 30°N-66°N, including fishing banks. Compass rose. Decorative title cartouche. Relief shown pictorially. Bar scale in French leagues. Aboriginal Peoples' territories are indicated on the map with text. Includes an index of geographical features and settlements. Includes notes. Shows a 1665 Northwest Passage survey route.